Treatment and Research Progress of Advanced Non-Small Cell Lung Cancer with Rare Mutations - Xiaoyue DU; Bo SHEN (Zhongliu Fangzhi Yanjiu, 2024)
With the development of precision medicine and genetic testing technologies, the treatment mode of non-small cell lung cancer (NSCLC) has shifted from the previous simple model to a complex personalized therapeutic strategy. Precise genetic typing has revolutionized NSCLC, transforming it from a disease into a highly heterogeneous group of diseases, emphasizing thecritical need for individualized treatment plans. Rare mutation groups that were previously overlooked are currently receiving greater attention in personalized treatment approaches. In recent years, various treatment methods targeting rare mutations, such as small-molecule inhibitors, immunotherapy, and antibody-drug conjugates, have continuously emerged, bringing new hope to patients with rare mutations. This article aims to elucidate the latest research findings and treatment strategies for rare mutations in advanced NSCLC, expecting to contribute to achieving precise and personalized treatment approaches, thereby improving the quality of life and prognosis of patients.